ANALYSIS OF STUDENTS’ SPEECH DELIVERY IN PUBLIC AND ACADEMIC SPEAKING CLASS OF THE FIFTH SEMESTER TBI STUDENTS 2023 BATCH AT STATE ISLAMIC UNIVERSITY OF DATOKARAMA PALU - Afifah, Afifah; Nur Asmawati (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2024)
This is qualitative research to analyze speech delivery of 26 fifth semester students of English Tadris Study Program 2023 Batch at State Islamic University of Datokarama Palu. There are two research questions: (1) How did the students deliver speeches in public and academic speaking class? and (2) What difficulties the students face in delivering speeches? The researchers applied observation and interview as the instruments. The observation was conducted for five meetings, while the interview is a structured interview consisting of five questions. From the observation, several points are highlighted. The students opened their speeches with greetings, questions, quotes, statements, rhymes, and jokes. Eye contact maintenance improved as they could maintain nervousness. Facial expressions and hand gestures also become their attention in every meeting. At first, they still performed hand crossing on chest, pointing, scratching, and hand lifted on hips. However, they did better on the next meetings. They could adjust their voice tone with the content of speech. The students ended up their speech with quotes, questions, poems, jokes, and persuasive statements. Some errors in pronunciation and repetitive words occur while the students deliver speeches. From the interview, the students found it hard to remember key points in their speech script. The students state that nervousness is their biggest problem besides lack of confidence when delivering speeches. However, they could perform well and reduce their nervousness whenever they prepare and practice well.